THE LANGUAGE ACQUISITION OF DAILY WORDS IN EARLY CHILDHOOD (2 YEARS OLD) - PASARIBU, CINTANA MARITO; DIANTI, HILMINA RAHMA; PUTRI, INTAN CAHYANI; NARGIS, NARGIS (Media Inovasi Pendidikan dan Publikasi, 2024)
This research addresses early childhood language acquisition (2 years old) with a focus on the acquisition of everyday words. The process of language acquisition involves both biological and social factors, in which interaction with the environment plays an important role. Children learn their first language through everyday communication, not formal teaching. This study used a qualitative descriptive method to observe and analyze the phonology of words produced by 2-year-old Salman. The results showed that children at this age experience rapid language development, with the most frequently used words related to daily needs such as food, body parts, and family members. These findings are important for parents, educators, and researchers in supporting children's optimal development.